Evaluation and Perception of an Edpuzzle Class Compared with a Traditional Class among Oral Radiology Undergraduate Students - Zain-Alabdeen, Ebtihal Habeeb (European Journal of General Dentistry, 2023)
Objectives Dental students are to an increasing extent presented with new digital learning technologies, especially online delivery of class content. Edpuzzle is a web-based eLearning application that allows educators to select subject-related videos and customize them by editing, cropping, voice-over recording, and adding questions directly to the video stream. Under the teacher's guidance, students log into Edpuzzle using their iPads, take the class, and answer questions. The aim of this study was to compare an Edpuzzle class with a traditional class for undergraduate oral radiology students in order to evaluate the educational effectiveness of each teaching method.Materials and Methods The study sample comprised 20 fourth-year dental students who agreed to participate in the study. A traditional class developed a differential diagnosis topic with pre- and post-knowledge tests. A second differential diagnosis topic was developed for an Edpuzzle class, also with a pre- and post-knowledge test. After the two classes were given, a Google Forms feedback questionnaire was sent to the students to evaluate their perceptions and preferences regarding the two classes. The educational effectiveness of each class type was evaluated by comparing means and analyzing the feedback questionnaires.Statistical Analysis The Wilcoxon signed-rank test was used to examine pre- and post-knowledge for each class, and Welch's t-test was used to test for differences in means of post-knowledge of both classes.Results Students in both classes obtained significantly better scores in the posttest than they did in the pretest (p = 0.0001). However, the differences in means of post-knowledge of both classes showed no significant differences (p = 0.0975). The feedback questionnaire showed higher percentages of positive attitude toward Edpuzzle class.Conclusion As a first-time experience, the Edpuzzle class interested most of the students. Workshops for the staff are needed to become expert in these technologies and to overcome any obstacles in implementing them for undergraduate dental students.
Keywords: Edpuzzle; dental; radiology; blended learning; undergraduate; videos; computer-aided instruction